Livestock farming sustainability and forage production in volcanic-hazard prone areas of Indonesia’s active volcano - Khalil, K.; Ananta, D.; Novia, R.; Suyitman, S.; Achmadi, J. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
Volcanic eruptions have varied and complex impacts on small-scale livestock farming located in volcanic hazard-prone areas due to diverse stock, rearing, and feeding practices. The study was aimed to clarify the critical factors for designing forage recovery and sustainable livestock production in highrisk-prone areas of active volcanic mountains. A total of seventy-five ruminant livestock farmers located in the eruption-impacted areas of five active volcanoes were surveyed on flock size, rearing, and feeding practices. They were interviewed about their experiences of the eruption's impact on the animals, forage feed, and livestock mitigation regarding survival efforts. Forage plants and soil samples were collected to analyze dry matter and crude nutrient composition and estimate the botanical composition, biomass production, and carrying capacity. Results showed that there were five species of ruminant animals reared in small flock size (< 7 heads/farm): beef cattle, buffalo, horses, goat, and sheep. Beef cattle and goats were the most popular farm animals raised in different breeds, rearing, and feeding systems. The volcanic eruption caused animal loss and health problems due to exposure to volcanic materials, forage damages, and animal mitigation constraints, resulting in flock size decrease and economic loss. The impact of the eruption on farm animals and forage plants varied among the volcanoes due to diverse eruptive characteristics, stock breed, rearing, and feeding practices. Livestock farming recovery post-eruption depended largely on the survival flock and the regrowth of forage plants. In conclusion, sustainable beef cattle farming in volcanic hazard-prone areas might be realized by effective livestock mitigation efforts, selecting appropriate types of animals and rearing/feeding systems based on agroecological conditions, and improving forage capacity and survival rate during and posteruption.